2015
DOI: 10.1016/j.cell.2015.08.017
|View full text |Cite
|
Sign up to set email alerts
|

A Synergistic Interaction between Chk1- and MK2 Inhibitors in KRAS-Mutant Cancer

Abstract: Cell 162, 146-159; July 2, 2015) Our paper presented a new algorithm, named PreCISE, designed to identify synergistic drug interactions that are effective at killing cancer cells harboring specific driver mutations. Using this platform and a cell-line-based screen, we identified a synergistic drug interaction between Chk1-and MK2 inhibitors in KRASor BRAF-driven cells, and that combination of therapy focused on these two kinase inhibitors is effective at inducing cell death of KRASand BRAF mutant tumors in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 0 publications
2
43
0
1
Order By: Relevance
“…MK2 inhibition may also be a potential target for combination therapies. Although we showed MK2 inhibition does not directly induce tumor cell apoptosis, inhibiting both MK2 along with the cell cycle promoter Chk1 results in tumor cytotoxicity across multiple therapy‐resistant cell lines . In a model of non‐small‐cell lung cancer, MK2 inhibition sensitized p53‐deficient tumors to cisplatin treatment .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…MK2 inhibition may also be a potential target for combination therapies. Although we showed MK2 inhibition does not directly induce tumor cell apoptosis, inhibiting both MK2 along with the cell cycle promoter Chk1 results in tumor cytotoxicity across multiple therapy‐resistant cell lines . In a model of non‐small‐cell lung cancer, MK2 inhibition sensitized p53‐deficient tumors to cisplatin treatment .…”
Section: Discussionmentioning
confidence: 65%
“…MK2 may have a significant effect on one or more of these areas within CRC so further investigation is warranted. MK2 also participates in cell cycle/proliferation pathways, which may support its importance in survival and therefore could be a potential therapeutic target of interest . In glioblastoma cells, MK2 activity regulates the protumor protein Khsrp and induces secretion of IL‐6, which promotes tumor growth and invasion in glioblastoma .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this effect was observed in cells that harbored KRAS mutations, a subset of CRCs particularly difficult to target and treat (Manic et al ., ). An independent study also observed efficacy of CHK1 inhibition in KRAS‐ mutated lung and colon adenocarcinoma cells, especially when combined with MK2 inhibitors (Dietlein et al ., ). MK2 functions in a pathway parallel to CHK1 and is responsible for maintaining cell cycle checkpoints in response to stress (Reinhardt et al ., ).…”
Section: Alternative Dna Repair‐targeting Therapies For Use In Colorementioning
confidence: 97%
“…MK2 functions in a pathway parallel to CHK1 and is responsible for maintaining cell cycle checkpoints in response to stress (Reinhardt et al ., ). KRAS ‐mutated cells exhibit intrinsic genotoxic stress that leads to constant activation of CHK1 and MK2, and inhibition of these proteins induced mitotic catastrophe in vitro , in murine cancer models, and in patient‐derived cells (Dietlein et al ., ). CHK1 inhibitors might be tested in KRAS ‐mutated CRC, a subset that currently has limited therapy options.…”
Section: Alternative Dna Repair‐targeting Therapies For Use In Colorementioning
confidence: 99%
“…Lastly, almost all ABC‐DLBCLs display BCL2 amplification/overexpression , suggesting that BCL2 inhibitors, such as venetoclax, which displays remarkable activity in CLL , should be evaluated in ABC‐DLBCL both as single agents, but particularly in combination with agents targeting chronic active BCR signaling (BTK‐, PI3Kδ‐, SYK‐ and PKC‐ β inhibitors), the CBM complex (MALT1 inhibitors), the Myddosome (IRAK4 inhibitors), and JAK/STAT3 signaling. When designing experiments to address potential synergistic drug interactions, appropriate additivity models should be carefully chosen . Overall, there is a large and mostly unchartered space for the use of novel, targeted drugs in ABC‐DLBCL, which should be systematically explored using novel, autochthonous mouse models and carefully stratified clinical trials.…”
Section: Therapeutic Implications Derived From Genomic Insights In Abmentioning
confidence: 99%